ANALISIS PERAN PELATIHAN DALAM MENINGKATKAN PRESTASI KERJA KARYAWAN PADA PERUSAHAAN BATA RINGAN JAYABRIX LAMONGAN - Ahmad Yani Syaikhudin; Ahmad Fathur Rozi (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
Today the industry is growing and developing rapidly in various places. The purpose of establishing these industries is inseparable from the objectives to be achieved by the company. These objectives include to obtain large profits with minimal production costs. The